Campaña de concientización, a través de la función emotiva, sobre la ansiedad en adolescentes de la Unidad Educativa Ambato - Villarroel Barreto, Melany Liseth (2025)
The project "Awareness Campaign Through the Emotive Function on Anxiety in Adolescents at Unidad Educativa Ambato" aims to proactively address and bring visibility to a critical issue in the educational field. Through a strategy of visual communication and emotive messages, the campaign seeks to raise awareness among students, teachers, and parents about anxiety, promoting its understanding, prevention, and proper management. This initiative also highlights the importance of distinctive visual identity and interactive tools that facilitate access to information and emotional connection within the educational community. Furthermore, it prioritizes interdisciplinary collaboration to foster a safe and empathetic environment, contributing to the socio-emotional well-being and academic performance of adolescents. Grounded in a qualitative approach, the project is based on thorough research and leverages graphic design as a key tool for social and educational transformation.